Genotype and phenotype in 12 additional individuals with SATB2‐associated syndrome. Issue 4 (7th March 2017) - Zarate, Y.A.; Kalsner, L.; Basinger, A.; Jones, J.R.; Li, C.; Szybowska, M.; Xu, Z.L.; Vergano, S.; Caffrey, A.R.; Gonzalez, C.V.; Dubbs, H.; Zackai, E.; et al.
Abstract : SATB2 ‐associated syndrome (SAS) is a multisystemic disorder caused by alterations of the SATB2 gene. We describe the phenotype and genotype of 12 individuals with 10 unique (de novo in 11 of 11 tested) pathogenic variants (1 splice site, 5 frameshift, 3 nonsense, and 2 missense) in SATB2 and review all cases reported in the published literature caused by point alterations thus far. In the cohort here described, developmental delay (DD) with severe speech compromise, facial dysmorphism, and dental anomalies were present in all cases. We also present the third case of tibial bowing in an individual who, just as in the previous 2 individuals in the literature, also had a truncating pathogenic variant of SATB2 . We explore early genotype‐phenotype correlations and reaffirm the main clinical features of this recognizable syndrome: universal DD with severe speech impediment, mild facial dysmorphism, and high frequency of craniofacial anomalies, behavioral issues, and brain neuroradiographic changes. As the recently proposed surveillance guidelines for individuals with SAS are adopted by providers, further delineation of the frequency and impact of other phenotypic traits will become available. Similarly, as new cases of SAS are identified, further exploration of genotype‐phenotype correlations will be possible. Abstract :